2014
DOI: 10.1007/7651_2014_168
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Modeling of Alcohol-Induced Liver Injury Using Human-Induced Pluripotent Stem Cells

Abstract: Alcohol consumption has long been associated with a majority of liver diseases and has been found to influence both fetal and adult liver functions. In spite of being one of the major causes of morbidity and mortality in the world, currently, there are no effective strategies that can prevent or treat alcoholic liver disease (ALD), due to a lack of human-relevant research models. Recent success in generation of functionally active mature hepatocyte-like cells from human-induced pluripotent cells (iPSCs) enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“… 116 More recently, it was observed that exposure to ethanol at the pathophysiological dosage induced apoptosis during differentiation of human iPSC-derived endoderm cells into hepatic progenitor cells and significantly reduced proliferative activity of mature stage hepatic cells. 123 Importantly, increased amounts of lipid droplets were detected in ethanol-treated iPSC-derived hepatocytes compared to controls, indicating the possibility of modeling ALD using human iPSCs.…”
Section: Response To Steroidsmentioning
confidence: 97%
See 1 more Smart Citation
“… 116 More recently, it was observed that exposure to ethanol at the pathophysiological dosage induced apoptosis during differentiation of human iPSC-derived endoderm cells into hepatic progenitor cells and significantly reduced proliferative activity of mature stage hepatic cells. 123 Importantly, increased amounts of lipid droplets were detected in ethanol-treated iPSC-derived hepatocytes compared to controls, indicating the possibility of modeling ALD using human iPSCs.…”
Section: Response To Steroidsmentioning
confidence: 97%
“… 111 In recent years, human iPSCs have been generated from diverse human somatic cells, 112 117 and these cells can then be differentiated into a spectrum of mature human cell types, including functional hepatocytes. 112 114 , 116 , 118 123 This development has enabled us to access an unlimited supply of hepatocytes, which was one of the major challenges in the past. Moreover, human iPSCs retain the same genetic information of the donor (i.e., patient) tissues, making iPSCs a promising resource to study human diseases.…”
Section: Response To Steroidsmentioning
confidence: 99%
“…2,4 Lately, many research papers have described the generation of patient-and disease-specific human iPSC lines and have further modeled these liver diseases. [15][16][17][18][19][20][21][22][23][24] Disease-and patientspecific human iPSCs of glycogen-storage-disease, familial-hypercholesterolemia, and a-1-antitrypsin (AAT) deficiency liver disease have recapitulated important disease-specific pathological features and key disease phenotypes in vitro. 2,[15][16][17] Likewise, the restored function in the patient iPSC-derived hepatocytes in genetically corrected AAT-deficiency patient iPSC lines provides hope for future gene therapy.…”
Section: Liver Disease Modeling Using Human Ipscsmentioning
confidence: 99%
“…24 The use of human iPSC-derived hepatocytes to model and evaluate alcohol-induced liver injury in vitro have reported that alcohol negatively influence liver progenitor formation and proliferation of hepatocytes. 21,22 Interestingly, alcohol exposure appears to increase alcoholic liver disease associated phenotypes such as steatosis and HCC markers in the mature stage hepatocytes derived from human iPSCs. 21 More recently, human iPSC-derived hepatobiliary cells have been utilized to model biliary atresia and biliary fibrosis.…”
Section: Liver Disease Modeling Using Human Ipscsmentioning
confidence: 99%
“…Alcohol-mediated changes in NMDA receptor function was also assessed in iPS-derived neural cells [83], indicating that iPSCs may offer a novel approach for better understanding the molecular mechanisms of alcohol use disorders [73, 84]. Exposure of iPSc to alcohol (100 mM) was also demonstrated to induce apoptosis and impair hepatic differentiation [85]. …”
Section: Effects Of Alcohol On Different Types Of Stem Cellsmentioning
confidence: 99%